2018
DOI: 10.1002/jso.25250
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy based on fluorodeoxyglucose‐positron emission tomography for managing liver metastasis from colorectal cancer

Abstract: Background Prognostic models are needed to manage liver metastasis from colorectal cancer (CRLM). Thus, we developed an algorithm to guide treatment based on the standardized uptake value (SUV) from fluorodeoxyglucose‐positron emission tomography (FDG‐PET). Methods We retrospectively evaluated 148 patients who underwent surgery for CRLM, including 107 cases of primary surgery and 41 cases with preoperative chemotherapy before conversion surgery. We evaluated the prognostic value of perioperative SUV among prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…21,23 In colorectal cancer and in CRLM, the prognostic value of 18 FDG-PET/CT has also been demonstrated, but its value in association with a clinical score has not yet been explored. 20,[24][25][26][27][28] We first observed that individual preoperative clinicopathological factors, CRS scores, and high-and low-risk CRS were not significantly different between patients who had the opposite postoperative oncological outcomes, confirming the poor prognostic accuracy of traditional clinical surrogates. 16,30 In contrast, all metabolic parameters, including SUV max and SUV peak , with the exception of MTV, were significantly increased in the patients who rapidly relapsed as compared with the patients with prolonged RFS, suggesting that metabolic characteristics could potentially predict the benefit of surgery in individual cases.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…21,23 In colorectal cancer and in CRLM, the prognostic value of 18 FDG-PET/CT has also been demonstrated, but its value in association with a clinical score has not yet been explored. 20,[24][25][26][27][28] We first observed that individual preoperative clinicopathological factors, CRS scores, and high-and low-risk CRS were not significantly different between patients who had the opposite postoperative oncological outcomes, confirming the poor prognostic accuracy of traditional clinical surrogates. 16,30 In contrast, all metabolic parameters, including SUV max and SUV peak , with the exception of MTV, were significantly increased in the patients who rapidly relapsed as compared with the patients with prolonged RFS, suggesting that metabolic characteristics could potentially predict the benefit of surgery in individual cases.…”
Section: Discussionmentioning
confidence: 79%
“…[21][22][23] In CRLM, several studies have also demonstrated the prognostic value of the metabolic parameters measured during preoperative 18 FDG-PET/CT. 20,[24][25][26][27][28] In the present study, we analyzed whether baseline 18 FDG-PET/ CT metabolic characteristics of CRLM may serve to discriminate between patients who will obtain a significant oncological benefit from surgery and those who will not. In addition, we evaluated the potential predictive value of a new score, combining metabolic data with standard CRS.…”
Section: Introductionmentioning
confidence: 99%
“…The use of 18F-FDG PET/CT enables the differentiation between normal and tumor tissue on the basis that neoplastic cells have higher glucose metabolic activity (18,19). The use of 18F-FDG PET/CT for oncological imaging is well established and widely accepted for many types of malignancies, and we have reported the clinical usefulness of 18-FDG PET/CT in assessing the malignant potential of some hepatobiliary pancreatic tumors (20)(21)(22).…”
Section: Discussionmentioning
confidence: 98%
“…5 We previously reported that the maximal standardized uptake value (SUVmax) and SUV change ratio are treatment factors for colorectal cancer liver metastasis. 6 Meanwhile, few studies have reported on the clinical value of FDG-PET in ampullary tumors. The differential diagnosis of benign or malignant 7,8 and the correlation between histological type and FDG uptake have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the maximal standardized uptake value (SUVmax) and SUV change ratio are treatment factors for colorectal cancer liver metastasis 6 . Meanwhile, few studies have reported on the clinical value of FDG‐PET in ampullary tumors.…”
Section: Introductionmentioning
confidence: 99%